THE MESOZOIC OF MEXICO AND NORTHWESTERN CENTRAL AMERICA - MULLERRIED, FEDERICO KG (Universidad Guadalajara, GUADALAJARA, JALISMO, MEX, 1854)
The name "mexicain" is proposed for this enzyme prepn, derived from the latex of an arboraceous plant (Caricaceae) about 8 ft tall The prepn compares favorably with papain
REV SOC EST ASTR GEOF
Keywords: MESOZOIC, MEXICO, NORTHWESTERN CENTRAL AMERICA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL